1993
DOI: 10.1007/bf00656532
|View full text |Cite
|
Sign up to set email alerts
|

Wheat straw, a potential substrate for cellulase production usingTrichoderma reesei

Abstract: Wheat straw, pre-treated with either alkali or steam, or both together, was used 46% more efficiently byTrichoderma reesei than untreated straw. Carboxymethyl cellulase and filter paper cellulase were higher by 52% and 74%, respectively, in the treated substrate compared with the untreated one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…reesei RUT-C30 is one of the most powerful and best characterized cellulolytic strains and is considered as a model cellulase producer [10][11][12]. Numerous industrial and agricultural residues have been evaluated for cellulase production using SSF by T. reesei [10][11][12][23][24][25].…”
Section: Hydrolytic Potential Of the Crude Enzyme Complex Produced Unmentioning
confidence: 99%
See 1 more Smart Citation
“…reesei RUT-C30 is one of the most powerful and best characterized cellulolytic strains and is considered as a model cellulase producer [10][11][12]. Numerous industrial and agricultural residues have been evaluated for cellulase production using SSF by T. reesei [10][11][12][23][24][25].…”
Section: Hydrolytic Potential Of the Crude Enzyme Complex Produced Unmentioning
confidence: 99%
“…Crude cellulase complex production from HW by solid state fermentation: The production of cellulase has been widely studied in submerged culture processes, but SSF has begun to become more popular mainly due to its advantages over submerged fermentation, including low capital investment, solid waste management, reduced energy requirements, improved product recovery, etc. [7][8][9][10][11]. In our previous study, an attempt had been made to develop a suitable and cost-effective process for the production of cellulolytic and hemicellulolytic enzymes using HW as the solid substrate and employing Trichoderma reesei, a fungus that has been extensively studied for cellulase production [12].…”
Section: Introductionmentioning
confidence: 99%
“…Canevascini and Gattlen (1981) observed that complete cellulase production was essential for efficient cellulose degradation. Though the cellulase activities were maximum on the 25 th day of SSF in all the monocultures and co-cultures, the rate of cellulose utilization decreased after the 20 th day, indicating that there was no relationship between cellulase production and substrate utilization as was observed earlier for T. reesei growing on wheat straw (Maheswari et al, 1993).…”
Section: Resultsmentioning
confidence: 83%
“…The contents of the flasks were removed periodically at an interval often days from the 5 th day of SSF (Simultaneous Saccharification Fermentation) and were analyzed for cellulose (Updegraff, 1969) reducing sugars (Maheswari et al, 1993) and protein (Lowry et al, 1951). The activities of enzymes, CMCase (Carboxymethylcellulase), FPase (Filter Paper Cellulase) and β-glucosidase (Ray et al, 1993) were assayed at an interval of five days.…”
Section: Methodsmentioning
confidence: 99%
“…The maximum cellulase activity was achieved when Trichoderma viride strains were cultivated in medium set to a range of pH 5–6; as pH increased up to 5.5, the hyper activities of exoglucanase (2.16 U/ml), endoglucanase (1.94 U/ml) and β-glucosidase (1.71 U/ml) were observed (Gautam et al 2010). Similarly, Maheswari et al (1993) made an observation that acidic pH-5.5 was found to be optimal for maximal cellulase production. The initial pH of the culture medium had marked effect on cellulase production by the different organisms.…”
Section: Resultsmentioning
confidence: 92%